Pembatasan Kebijakan Ekspor Batu Bara Bagi Perekonomian Indonesia - Angela Vidya Octaviani; Azra Nabila; Fahmy Mayadi; Muhammad Zein Saleh (Universitas 45 Surabaya, 2025)
This research aims to analyze the impact of the Indonesian government’s coal export restrictions on the national economy, particularly focusing on the effects on trade, industry, and energy supply. The export restrictions, which were implemented to prioritize domestic energy needs, aim to ensure sufficient coal supply for domestic power plants and support energy security. Data shows that despite Indonesia being one of the world's largest coal exporters, the restrictions have resulted in a significant decrease in export revenues, which could potentially reach up to USD 3 billion per month. Furthermore, the policy creates challenges for coal producers due to disruptions in cash flow and rising operational costs, such as demurrage charges. However, the restrictions also serve as a strategic move to reduce dependence on fossil fuels and encourage the development of the domestic coal processing industry. This research highlights the balance between maintaining economic growth through international trade and ensuring national energy sustainability. By managing these policies effectively, Indonesia can strengthen its position in the global coal market while supporting long-term energy resilience and sustainable economic growth.